Problems of river degradation in the Kathmandu Valley - Pradhananga, R. P. (Journal of Nepal Geological Society, 2000)
The speedy degradation of rivers in the Kathmandu Valley has led to the failure of bridges, historical sites, and riverbanks. The present ad hoc practice of constructing protection measures has to be given a second thought. An integrated approach including engineering, legal, and social aspects can stop the speedy degradation of rivers. The proposed engineering measures include short-, medium-, and long-term stabilisation of the Chobhar Gorge including the construction of a series of check dams at a regular interval. The legal and other measures include banning sand extraction, construction of riverside road, preventing encroachment of floodplain, reducing sand demand, controlling the discharge of acidic effluents into the river, and creating awareness.